Confrontation, Competition, or Cooperation? The China–US Relations Represented in China Daily's Coverage of Climate Change (2010–2019). Issue 1 (4th March 2022) - Fu, Xiaoli; Wang, Guofeng
ABSTRACT: In contrast with the vital role China has played in global climate governance in recent years, it is rare to see the research on its foreign-language media representation of this issue. Drawing on critical discourse analysis and corpus linguistics, this study examines how China's flagship English-language newspaper China Daily communicates climate change (2010–2019) to international audiences and how it represents China and the US as well as China–US relations regarding climate issues. Results show that through the use of specific modalities and other collocates of China and the US, the newspaper constructs China as a responsible major country and the US as a capricious and self-centered nation while emphasizing the importance of their cooperation on climate actions. The ways it represents this issue can be interpreted with regard to pragmatism and the China Dream of national rejuvenation endorsed by the Chinese government. To have a stable environment for sustainable development of China and the whole world, China is willing to avoid confrontation and work together with the US and other countries in combating climate change though competition may remain in such related fields as green energy, as indicated by China Daily .